PENGARUH RETURN ON INVESTMENT OF HUMAN CAPITAL (ROIHC), EFEKTIFITAS TERHADAP KINERJA ORGANISASI STUDI KASUS PADA PT TGU TIRTATAMA JAKARTA - BASUKI RANTO (Universitas Negeri Jakarta, 2010)
The purpose of research is to determine the effect of Return On Investment of Human Capital (ROIHC), Effectifity with Performance Organization. A survey was conducted at the PT TGU Tirtatama once of entreprises who distibution activity. The research concludes that there are as follow : (1) there is direct effect of the ROIHC on performance organization, (2) there is direct effect of the effectivity on performance organization , (3) Moreover there is direct effect between the ROI of human capital, effectivity perception with the performance organization. Therefore, the performance organization can be improved by enhancing through the ROI of human capital and effectivity.